Jogja Heritage Track as an Indirect Visitor Management Instrument in the Unesco Heritage Area of the Yogyakarta Philosophical Axis - Fitria Noviati; Gefira Mokoginta; Amin Kiswantoro (Syntax Literate, 2026)
The designation of the Yogyakarta Philosophical Axis as a UNESCO World Heritage Site has increased the need for an effective visitor management strategy to balance tourism use, visitor experience, and cultural heritage conservation. This study aims to examine the role of Jogja Heritage Track (JHT) as an indirect visitor management instrument within the UNESCO Heritage Area of the Yogyakarta Philosophical Axis. Employing a qualitative descriptive case study approach, data were collected through semi-structured interviews, participant observation, and documentation involving program managers, repeat visitors, first-time visitors, and independent tourists. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that JHT performs two complementary functions. First, it serves as a heritage interpretation platform that enhances visitors’ understanding of the historical, cultural, and philosophical significance of the heritage area. Second, it functions as a tourist mobility management mechanism through predetermined routes, scheduled departures, and structured visitation patterns that guide visitor movement. The study further reveals that the integration of heritage interpretation and tourist mobility contributes to visitor management outcomes by shaping visitor cognition, increasing awareness of heritage values, encouraging responsible behavior, and facilitating more organized tourism experiences. These findings suggest that heritage-based transportation programs can function beyond their conventional transportation role and serve as indirect visitor management instruments within heritage destinations. The study contributes to destination management literature by demonstrating how educational and mobility-based interventions can be integrated to support sustainable visitor management in UNESCO heritage areas.